2021 Physics Education Research Conference Proceedings 2021
DOI: 10.1119/perc.2021.pr.randolph
|View full text |Cite
|
Sign up to set email alerts
|

Impact of informal physics programs on female university students

Abstract: Informal physics programs can play a vital role in supporting student learning and sense of community beyond the formal settings of a classroom or laboratory. This work builds on a recent study of the impact of facilitating informal physics programs on students' physics identity, sense of belonging, and career skills development by narrowing the focus to specifically examine effects on female students who are underrepresented in physics. We found a statistically significant shift in confidence of choice of maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The impact of these disadvantages can be seen in female students' physics identity, their sense of belonging, and their desire to persist in the field. Recent studies have shown that students who facilitate informal physics programs can experience positive gains to their physics identity [54,55,57,58]. Our previous work [55] suggested that these gains may particularly address challenges faced by female physics students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of these disadvantages can be seen in female students' physics identity, their sense of belonging, and their desire to persist in the field. Recent studies have shown that students who facilitate informal physics programs can experience positive gains to their physics identity [54,55,57,58]. Our previous work [55] suggested that these gains may particularly address challenges faced by female physics students.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased interest in understanding how student participation in informal physics programs provides a platform for the development of physics identity and aids in building a sense of community [52][53][54][55][56][57][58], which are constructs potentially critical for female students' success, retention, and persistence in physics. Informal physics programs are less structured and vary in frequency, scale, or target audience scale [59].…”
Section: Introductionmentioning
confidence: 99%
“…The survey research design employed 32 students aged ranges from 13-14 years belonging to rural areas in the United States. Based on self-reported data, Randolph, Hay, Rethman, Erukhimova, Donaldson, and Perry (2021) 􀅫indings demonstrate that students who led informal physics programs positively shaped their physics identities, felt more a part of the physics community, and gained 21st-century career skills. Students speci􀅫ically mentioned improved communication, teamwork and networking, and design skills.…”
Section: Signi􀅮icance Of Studymentioning
confidence: 99%